(untitled) (African Human Mobility Review, 2021)
This paper examines how African migration to the European Union (EU) has become externalized and securitized and the implications this has for migration management for both the EU and Africa. To accomplish this, the paper employed a qualitative research approach which reviewed current literature on the topic under study. It found that the externalization and securitization of African migration to the EU have failed to prioritize and address the different socio-economic and political conditions that are driving irregular migration. Additionally, externalization and securitization as policy responses do not stop irregular African migration; rather, they prolong the misery of migrants who are at the mercy of smugglers who prey on their desperation. The paper concludes that migration management between the EU and Africa needs to be anchored on policies that address the core ‘push’ factors driving irregular migration from Africa, rather than policies which do not stop migration (even though they have slowed it down) but rather indirectly empower smugglers and leave considerable room for the abuse of migrants.